2015
DOI: 10.1002/jobm.201400813
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the native form and the carboxy‐terminally truncated halotolerant form of α‐amylases from Bacillus subtilis strain FP‐133

Abstract: Two amylases, amylase I and amylase II from Bacillus subtilis strain FP-133, were purified to homogeneity and characterized. Their stabilities toward temperature, pH, and organic solvents, and their substrate specificities toward polysaccharides and oligosaccharides were similar. Under moderately high salt conditions, both amylases were more stable than commercial B. licheniformis amylase, and amylase I retained higher amylase activity than amylase II. The N-terminal amino acid sequence, genomic southern blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Halo-tolerance is an important property of industrial enzymes (Yan et al, 2009;Takenaka et al, 2015). Halophilicity may be attributed to the ability of the protein amino acid residues to resist the destabilizing effect of surrounding electrolytes, and most of the halo-tolerant proteins have been described to have similar sequences dominated by acidic residues (Graziano and Merlino, 2014).…”
Section: Modification For Halophilicity and Thermostabilitymentioning
confidence: 99%
“…Halo-tolerance is an important property of industrial enzymes (Yan et al, 2009;Takenaka et al, 2015). Halophilicity may be attributed to the ability of the protein amino acid residues to resist the destabilizing effect of surrounding electrolytes, and most of the halo-tolerant proteins have been described to have similar sequences dominated by acidic residues (Graziano and Merlino, 2014).…”
Section: Modification For Halophilicity and Thermostabilitymentioning
confidence: 99%
“…This strongly suggests that Amy2 and Amy3 could be derived from the proteolytic degradation of Amy 1, which may be due to the secreted proteolytic activity in the extracellular medium of the US586 strain. Moreover, it was demonstrated that the production of amylases isoforms by proteolysis had already been described for B. subtilis X‐23 (Kohji et al, ) and B. subtilis FP‐133 (Takenaka et al, ) displaying the same physicochemical properties.…”
Section: Resultsmentioning
confidence: 90%
“…Anti-salt or halotolerance is an important characteristic to evaluate whether the enzyme can be used in industrial processes1829. We used different concentrations of NaCl to monitor the halotolerance of KerSMD and its different variants (Fig.…”
Section: Resultsmentioning
confidence: 99%